Identification of Promising Glyphosate-Degrading Bacteria Isolated from the Rhizosphere of Local Chili Pepper Plantation - Lisdiana, Lisa; Maulida, Khilma Ziyadatur Rizka; Anissa, Ratih Khairul; Arista, Anggi Maulia (IKIP Mataram, 2025)
The glyphosate’s continuous application in agricultural fields has caused adverse environmental effects. Utilizing indigenous microorganisms as glyphosate-degrading agents can be an effective and eco-friendly solution. Isolate Cf2, obtained from a local chili pepper plantation in Indonesia, grew as a co-dominant isolate in media with 50 ppm glyphosate, indicating its potential as glyphosate-degrading bacteria. However, this isolate cannot be applied yet because it has not been identified. Identification can provide initial insights into the safety of indigenous isolates for ecological application. Thus, this study aims to identify isolate Cf2 by utilizing the 16s rRNA gene sequence as the genetic marker. The data was compared to the database using the web-based BLAST2 program (version 2.13.0). Then, the evolutionary relationship of this isolate with its closest relatives was assessed through phylogenetic tree reconstruction. The results demonstrate that the isolate Cf2 has a sequence similarity of 98.88% with Bacillus subtilis. The phylogenetic tree reconstruction further indicates that isolate Cf2 forms a monophyletic clade with this species. Hence, it can be concluded that isolate Cf2 is indeed B. subtilis. This study is the first report of glyphosate-degrading B. subtilis isolated from chili pepper plantations in Indonesia, offering a new insight into bioremediation strategies.